YEAST two-hybrid and itc studies of alpha and beta spectrin interaction at the tetramerization site - Sevinc, Akin (SP Versita, 2011)
Yeast two-hybrid (Y2H) and isothermal titration calorimetry (ITC) methods were used to further study the mutational effect of non-erythroid alpha spectrin (αII) at position 22 in tetramer formation with beta spectrin (βII). Four mutants, αII-V22D, V22F, V22M and V22W, were studied. For the Y2H system, we used plasmids pGBKT7, consisting of the cDNA of the first 359 residues at the N-terminal region of αII, and pGADT7, consisting of the cDNA of residues 1697–2145 at the C-terminal region of βII. Strain AH109 yeast cells were used for colony growth assays and strain Y187 was used for β-galactosidase activity assays. Y2H results showed that the C-terminal region of βII interacts with the N-terminal region of αII, either the wild type, or those with V22F, V22M or V22W mutations. The V22D mutant did not interact with βII. For ITC studies, we used recombinant proteins of the αII N-terminal fragment and of the erythroid beta spectrin (βI) C-terminal fragment; results showed that the K(d) values for V22F were similar to those for the wild-type (about 7 nM), whereas the K(d) values were about 35 nM for V22M and about 90 nM for V22W. We were not able to detect any binding for V22D with ITC methods. This study clearly demonstrates that the single mutation at position 22 of αII, a region critical to the function of nonerythroid α spectrin, may lead to a reduced level of spectrin tetramers and abnormal spectrin-based membrane skeleton. These abnormalities could cause abnormal neural activities in cells.